2010
DOI: 10.1097/sap.0b013e3181bda312
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vasopressor Administration on the Outcomes of Microsurgical Breast Reconstruction

Abstract: The use of vasopressors during microsurgery is still debated. General anesthesia often induces hypotension, but microsurgeons are reluctant to use intraoperative vasopressors with the potential risks of vasoconstriction. A retrospective review was performed on 187 consecutive patients undergoing 258 deep inferior epigastric perforator flaps, free transverse rectus abdominis myocutaneous flap, and muscle-sparing free transverse rectus abdominis myocutaneous flap operations. A total of 102 patients (140 flaps) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 21 publications
4
63
2
Order By: Relevance
“…Again, the most commonly used vasopressors were phenylephrine and ephedrine. Our study, as well as the studies by Monroe et al 5 and Chen et al, 6 are retrospective series that demonstrate no significant effect on major free tissue transfer complications with intraoperative vasopressor administration. However, each of these series, including our own, are likely underpowered to definitively answer the question.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Again, the most commonly used vasopressors were phenylephrine and ephedrine. Our study, as well as the studies by Monroe et al 5 and Chen et al, 6 are retrospective series that demonstrate no significant effect on major free tissue transfer complications with intraoperative vasopressor administration. However, each of these series, including our own, are likely underpowered to definitively answer the question.…”
Section: Discussionmentioning
confidence: 56%
“…The complete flap failure rate was 2.9% in the vasopressor group and 6.7% in the no-vasopressor group. Chen et al 6 published a study of 187 patients who underwent 258 free tissue transfers for breast reconstruction. Of the 187 patients, 102 (54.5%) received intraoperative vasopressor drugs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent literature showed that intraoperative use of vasopressors did not affect the rate of flap loss or reoperation [28]. The thought is that an attenuated pressor response occurs after surgical sympathectomy, which occurs during vessel dissection [29]. Dobutamine was found to improve flap flow and both dobutamine and norepinephrine improved free flap skin blood flow [30].…”
Section: Special Considerations Vasoactive Medicationsmentioning
confidence: 99%